Chronic Obstructive Pulmonary Disease: Safety and Tolerability of Hyperpolarized (129)Xe MR Imaging in Healthy Volunteers and Patients - Driehuys, Bastiaan (Radiological Society of North America, Inc., 2012)
PURPOSE: To evaluate the safety and tolerability of inhaling multiple 1-L volumes of undiluted hyperpolarized xenon 129 ((129)Xe) followed by up to a 16-second breath hold and magnetic resonance (MR) imaging. MATERIALS AND METHODS: This study was approved by the institutional review board and was HIPAA compliant. Written informed consent was obtained. Forty-four subjects (19 men, 25 women; mean age, 46.1 years ± 18.8 [standard deviation]) were enrolled, consisting of 24 healthy volunteers, 10 patients with chronic obstructive pulmonary disease (COPD), and 10 age-matched control subjects. All subjects received three or four 1-L volumes of undiluted hyperpolarized (129)Xe, followed by breath-hold MR imaging. Oxygen saturation, heart rate and rhythm, and blood pressure were continuously monitored. These parameters, along with respiratory rate and subjective symptoms, were assessed after each dose. Subjects’ serum biochemistry and hematology were recorded at screening and at 24-hour follow-up. A 12-lead electrocardiogram (ECG) was obtained at these times and also within 2 hours prior to and 1 hour after (129)Xe MR imaging. Xenon-related symptoms were evaluated for relationship to subject group by using a χ(2) test and to subject age by using logistic regression. Changes in vital signs were tested for significance across subject group and time by using a repeated-measures multivariate analysis of variance test. RESULTS: The 44 subjects tolerated all xenon inhalations, no subjects withdrew, and no serious adverse events occurred. No significant changes in vital signs (P > .27) were observed, and no subjects exhibited changes in laboratory test or ECG results at follow-up that were deemed clinically important or required intervention. Most subjects (91%) did experience transient xenon-related symptoms, most commonly dizziness (59%), paresthesia (34%), euphoria (30%), and hypoesthesia (30%). All symptoms resolved without clinical intervention in 1.6 minutes ± 0.9. CONCLUSION: Inhalation of hyperpolarized (129)Xe is well tolerated in healthy subjects and in those with mild or moderate COPD. Subjects do experience mild, transient, xenon-related symptoms, consistent with its known anesthetic properties. © RSNA, 2011 Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11102172/-/DC1